4 Towards fast tracking following paediatric cardiac surgery: strategy and initial experience with early extubation. (28th April 2017) - Pelella, G; Tiwari, N; Cuddihy, S; Raj, N; Lotto, A; Dhannapuneni, R; Guerrero, R
Abstract : Objective: The aim of this study is to report our initial experience with early extubation (<6 hours) following congenital cardiac surgery, assessing its efficacy and safety and the potential for fast tracking through Paediatric Intensive Care Unit (PICU). Methods: Early extubation was defined as intraoperative or within 6 hours from arrival to PICU. Between January 2014 to March 2016, 846 patients underwent congenital cardiac surgery at Alder Hey Children's Hospital with a 30 days mortality rate of 0.9%.The clinical records of 608 patients older than 90 days of age were reviewed. The mean age and weight was 13.1 month (5.6–57) and 8.9 kg (5.8–16.325) respectively. Re-do sternotomies accounted for 181 cases (29.7%). The management strategy involved a specific anaesthetic technique, warm cardiopulmonary bypass, and intraoperative echocardiogram for evaluation of surgical repair. Results: Out of 608 patients, early extubation was accomplished in 480 patients (78.9%) of which 337 pts (55%) were extubated in theatre. There was no mortality or other adverse event related to early extubation. Reintubation was required in 9 patients (1.4%). Patients extubated earlier had shorter PICU stay (1[1–2] vs 3.5 [2–7]days) and shorter hospital stays (5 [4–8] vs 12 [7–20] days). It was noted that PICU stay was artificially longer due to bottle-neck effect along the patient flow. Conclusion : Early extubation can be accomplished safely following cardiac operations in an age-selected paediatric population. It is associated with low morbidity, mortality with reduced PICU and Hospital length of stay. This preliminary study demonstrates that a fast-tracking model is feasible.